O curso de Pedagogia da UFES sob os olhares das/os alunas/os concluintes : processos de subjetivação produzidos num coletivo de intensidades - Bastos, Clara Melo Casotti (2014)
This thesis analyses the Pedagogy graduation course through the senior students’ perspective, approaching the subjectivities’ production as the central topic. It empowers the discourses through the undergraduates’ narratives on how they became teaches and pedagogues along the course, relating them to the curriculum prescriptions and the dimensions lived by them. It considers the curriculum a set of discursive and normative elements, conversations, and experiences sharing, and potentializes that through meetings, a formation to the other, and prescriptive gaps, as it forms a complex production of subjectivities, always collective, which struggles to abandon the clichés of meanings and the molarities of curriculum prescription. The main theoretical intercessors as we problematize the subjective productions on curriculum were Gilles Deleuze, Félix Guattari and Janete Magalhães Carvalho. This research used the cartography as a means to follow processes in which there is not any data collecting, but data production based on narratives, which are forms of conversations, as methodological sources. Therefore, the process became intense and delicate, but very happy, for having prioritized the many ways of living this curriculum, without an individualization of subjects, on the contrary, focusing on a decentered subjectivity’s perspective, without faces.